Use of the Location Inverse Solution to Reduce Ghost Images. (22nd November 2009) - Hu Hu, Yong-Zhong Yong-Zhong; Li Li, Ting-Jun Ting-Jun; Zhou Zhou, Zheng-Ou Zheng-Ou
Abstract : Through-the-wall imaging (TWI) is a difficult but important task for both law enforcement and military missions. Acquiring information on both the internal features of a structure and the location of people inside plays an important role in many fields such as antiterrorism, hostage search and rescue, and barricade situations. Up to now, a number of promising experimental systems have been developed to validate and evaluate diverse imaging methods, most of which are based on a linear antenna array to obtain an image of the objects. However, these methods typically use the backward projection (BP) algorithm based on ellipse curves, which usually generates additional ghost images. In this paper, the algorithm using the location inverse solution (LIS) to reduce the ghost images is proposed and simulated. The results of simulation show that this approach is feasible.